Analisis Dimensi dan Determinan Kualitas Kehidupan Kerja Perawat di Rumah Sakit: A Scoping Review - Auliyah Zahra Azizatunnisa; Irman Somantri; Khoirunnisa Khoirunnisa (Faletehan Health Journal, 2025)
Nurses constituted the largest workforce in the global healthcare system but faced challenges such as high workloads, limited decision-making autonomy, and a negative public image, all of which affected their quality of work life. This study aimed to map and analyze the quality of work life among hospital nurses and its influencing factors. A scoping review method was applied using the Arksey and O’Malley framework, guided by the PRISMA-ScR checklist. Literature was sourced from PubMed, Scopus, EBSCO, ScienceDirect, and Gscholar, focusing on full-text articles in English or Indonesian published between 2020 and 2025. Ten articles were included in the final review. Findings indicated that nurses’ quality of work life was generally at a moderate level. Among the four dimensions assessed, namely work life/home life, work design, work context, and work world, the highest scores were found in the work context dimension, while the lowest appeared in work life/home life and work world. Factors influencing these outcomes included age, gender, experience, workload, family responsibilities, shift patterns, and perceptions of the profession. This review highlighted the need for targeted organizational and policy-level strategies to improve nurses’ well-being at work.